Peran Efikasi Diri dan Dukungan Sosial: Membangun Niat Berwirausaha Generasi Z - Sri Karuniawati Retna Ningsih; Henky Lisan Suwarno (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
The high rate of unemployment among Generation Z shows that encouraging entrepreneurial ideas is important for creating new job opportunities. This study looks at how self-efficacy and social support affect the desire of Generation Z to start their own businesses. The research involved 150 participants, selected through purposeful sampling, and used a questionnaire with a 5-point scale to gather information. The data was analyzed using PLS-SEM and regression models. The results show that both self-efficacy and social support have a strong and positive effect on entrepreneurial intentions, whether looked at on their own or together. These results underscore the effectiveness of the combination of individual confidence and supportive social environments in fostering entrepreneurial intentions. Therefore, strengthening both internal and external factors is a key strategy in promoting an entrepreneurial mindset among Generation Z. The findings imply that efforts to develop internal potential and foster a positive social environment must be optimized to encourage entrepreneurship among Generation Z. Additionally, this study seeks to provide insights into the importance of self-efficacy and social support in shaping entrepreneurial intentions, serving as a basis for reflection in developing entrepreneurial potential within this generation.